2021
DOI: 10.1101/2021.06.01.446519
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Birth Order Differences in Education Originate in Post-Natal Environments

Abstract: Siblings share many environments and much of their genetics. Yet, siblings turn out different. Intelligence and education are influenced by birth order, where earlier-born outperform later-born. We investigate whether birth order differences in education are caused by genetic differences. Using data that spans two generations, combining registry, survey, and genotype information, this study is based on the Norwegian Mother, Father and Child Cohort Study (MoBa). We show that there are no genetic differences by … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…Full siblings have the same expected genetic endowments. It is possible that there could still be systematic differences if children's genetics affect subsequent fertility, but empirically this does not appear to be the case, as a number of studies have found no systematic genetic differences between siblings by birth order(Domingue et al, 2015;Muslimova et al, 2020;Isungset et al, 2021).2 For a discussion of the self-report method, its advantages and disadvantages, and a comparison to alternative assessment methods, seePaulhus et al (2007).…”
mentioning
confidence: 99%
“…Full siblings have the same expected genetic endowments. It is possible that there could still be systematic differences if children's genetics affect subsequent fertility, but empirically this does not appear to be the case, as a number of studies have found no systematic genetic differences between siblings by birth order(Domingue et al, 2015;Muslimova et al, 2020;Isungset et al, 2021).2 For a discussion of the self-report method, its advantages and disadvantages, and a comparison to alternative assessment methods, seePaulhus et al (2007).…”
mentioning
confidence: 99%